PENGARUH PERTUMBUHAN EKONOMI TERHADAP DISPARITAS PEMBANGUNAN DI PROPINSI SUMATERA SELATAN - Ningsih, Endang Kusdiah; Novianty, Dwi Eka; Ermeila, Sri (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2019)
Economic growth of any counties had positive and negative impact. A positive impact is an increase in national income and negatif impact are inequility of personal income distribution and development disparities. Economic growth in province of South Sumatera also had that impact. The purposes of this research is to prove empirically relationship and patterns of linkages between economic growth and development disparities. The data that used is secondary data obtained from Central Statistic Agency in the form of economic growth rates, gross regional domestic product per capita and total population of the province of South Sumatera during the period 2010-2017. The analysis use with Williamson Index to measure development disparities and Pearson Correlation to find out the relationship between economic growth and development disparities and to prove Kuznets hypothesis. The result of this analysis are : (1)development disparities in the province of South Sumatera during the period 2010-2017 , including height indicated by the Williamson Index more than 0,5. (2) Pearson Correlation is -0,253 show that there is a negatif relationship between economic growth and development disparities and this proved that the Kuznets hypothesis (curve U-Reserved) also occur happen in this province. It means, that economic growth is inversely proportional to development disparities.(3) R Square is 0,064 , means the effect ofeconomic growth on development disparities is 6% and 94% influenced by other factors